Gamma Irradiation Influences the Survival and Regrowth of Antibiotic-Resistant Bacteria and Antibiotic-Resistance Genes on Romaine Lettuce - Dharmarha, Vaishali; Guron, Giselle; Boyer, Renee R.; Niemira, Brendan A.; Pruden, Amy; Strawn, Laura K.; Ponder, Monica A. (Frontiers in Microbiology, 2019)
Contamination of romaine lettuce with human pathogens, antibiotic-resistant bacteria (ARB), and antibiotic resistance genes (ARGs) occurs during production. Post-harvest interventions are emplaced to mitigate pathogens, but could also mitigate ARB and ARGs on vegetables. The objective of this research was to determine changes to lettuce phyllosphere microbiota, inoculated ARB, and the resistome (profile of ARGs) following washing with a sanitizer, gamma irradiation, and cold storage. To simulate potential sources of pre-harvest contamination, romaine lettuce leaves were inoculated with compost slurry containing antibiotic-resistant strains of pathogenic (Escherichia coli O157:H7) and representative of spoilage bacteria (Pseudomonas aeruginosa). Various combinations of washing with sodium hypochlorite (50 ppm free chlorine), packaging under modified atmosphere (98% nitrogen), irradiating (1.0 kGy) and storing at 4ºC for 1 d versus 14 d were compared. Effects of post-harvest treatments on the resistome were profiled by shotgun metagenomic sequencing. Bacterial 16S rRNA gene amplicon sequencing was performed to determine changes to the phyllosphere microbiota. Survival and regrowth of inoculated ARB were evaluated by enumeration on selective media. Washing lettuce in water containing sanitizer was associated with reduced abundance of ARG classes that confer resistance to glycopeptides, β-lactams, phenicols, and sulfonamides (Wilcoxon, p<0.05). Washing followed by irradiation resulted in a different resistome chiefly due to reductions in multidrug, triclosan, polymyxin, β-lactam, and quinolone ARG classes (Wilcoxon, p<0.05). Irradiation followed by storage at 4ºC for 14 d led to distinct changes to the β-diversity of the host bacteria of ARGs compared to 1 d after treatment (ANOSIM, R=0.331; p=0.003). Storage of washed and irradiated lettuce at 4 ºC for 14 d increased the relative abundance of Pseudomonadaceae and Carnobacteriaceae (Wilcoxon, p<0.05), two groups whose presence correlated with detection of 10 ARG classes on the lettuce phyllosphere (p<0.05). Irradiation resulted in a significant reduction (~3.5 log CFU/g) of inoculated strains of E. coli O157:H7 and P. aeruginosa (ANOVA, p<0.05). Results indicate that washing, irradiation and storage of modified atmosphere packaged lettuce at 4ºC are effective strategies to reduce antibiotic-resistant E. coli O157:H7 and P. aeruginosa and relative abundance of various ARG classes.